Legal Protection of the Workers in Certain Time Agreement (Study at PT. Infomedia Nusantara) - Surya Nita (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Working relationships are formed as a result of an agreement between employers and workers. The agreement is reached after both parties talk / negotiate on the agreement to be made and based on the will of both parties. The problem that arises is the number of violations in the application of the system of certain time agreement (CTA). Many deviations occur on the implementation of CTA rules or in other words CTA that is implemented is not appropriate or even does not refer to the rules of CTA set out in the Manpower Act. In practice, in addition to the application of CTA which is not in accordance with the provisions stipulated in the Manpower Act, the CTA system implemented also greatly disadvantages the workers. The purpose of this research is to know the legal arrangement about certain time work agreement, due to certain time working agreement law, and legal protection to workers who are bound in certain time working agreement in PT. Infomedia Nusantara. The type of research used is empirical method, descriptive research, while data analysis in this study using qualitative methods. Based on the provisions of Article 56 paragraph (2) of Law Number 13 Year 2003 concerning Manpower referred to as certain time agreement (CTA) constitutes an employment agreement between workers or workers and employers to establish a working relationship within a certain time or for certain workers. As a result of the law of a certain time labor agreement regulates if either party terminates the employment relationship before the expiration of the period specified in a specified working period, the party terminating the employment relationship is ultimately required to pay compensation to the other party for the wanprestation of that party. Legal protection of workers who are bound in certain time work agreement in PT. Infomedia Nusantara is based on the Law Number 13 of 2003 on Manpower, where the worker must be protected from permanent work, that is, the CTA if told to do work that is not his job, the status of CTA by law or by law is no longer into CTA, but has changed its status to Worker / Laborer of Uncertain time agreement (UCTA), whose meaning is regarded as an employee / permanent worker.